2020
DOI: 10.1002/ajh.26000
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cytogenetic risk on the outcomes of allogeneic hematopoietic cell transplantation in patients with relapsed/refractory acute myeloid leukemia: On behalf of the acute leukemia working party (ALWP) of the European group for blood and marrow transplantation (EBMT)

Abstract: Karyotypic analysis at time of diagnosis has an important value in determining initial response to treatment, remission duration and overall survival (OS) in acute myeloid leukemia (AML). Less is known about its value before allogeneic hematopoietic cell transplantation (allo‐HCT) in patients transplanted with active disease, either relapsed or primary refractory (Rel‐Ref) AML. We explored the impact of cytogenetic risk (stratification according to MRC‐UK) in 2089 patients with either Ref (n = 972) or Rel AML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The present study also suggested that total therapy was associated with a TRM of 19.0% at 2 years and 22.1% at 5 years after transplantation. This result was comparable with those of previous studies conducted on patients with refractory or relapsed AML (2-year TRM: 19% vs. 16%-26%) [4][5][6][7][8] and on patients with AML in first complete remission (CR1) or CR2 (2-year TRM: 19.0% vs. 13.0%-20.0%) [15,33]. These results demonstrate the safety of total therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present study also suggested that total therapy was associated with a TRM of 19.0% at 2 years and 22.1% at 5 years after transplantation. This result was comparable with those of previous studies conducted on patients with refractory or relapsed AML (2-year TRM: 19% vs. 16%-26%) [4][5][6][7][8] and on patients with AML in first complete remission (CR1) or CR2 (2-year TRM: 19.0% vs. 13.0%-20.0%) [15,33]. These results demonstrate the safety of total therapy.…”
Section: Discussionsupporting
confidence: 88%
“…40.0%‐60.0% and 2‐ year LFS: 51.4% vs . 20.0%‐40.0%) [ 4 , 5 , 6 , 7 , 8 ]. Moreover, this result is also similar to that in patients with AML in second complete remission (CR2) (2‐year CIR: 29.5% vs .…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities at transplantation were determined using the hematopoietic cell transplantation‐specific comorbidity‐index (HCT‐CI) score 14 . Cytogenetic risk was stratified according to the MRC‐UK classification, as previously reported 15,16 …”
Section: Methodsmentioning
confidence: 99%
“…14 Cytogenetic risk was stratified according to the MRC-UK classification, as previously reported. 15,16…”
Section: Definitionsmentioning
confidence: 99%
“…Besides mutation in fms-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD), is also an important risk factor in R/R AML patients, being associated with worse outcomes. Poiani et al [30] explored the impact of cytogenetic risk on the outcomes of allo-HSCT in patients with R/R acute myeloid leukemia. They showed that compared to the favorable risk group, inter-mediate and adverse risk patients were associated with worse leukemia-free survival and OS and also with a higher incidence of relapse.…”
Section: Discussionmentioning
confidence: 99%